Predicting facial characteristics from complex polygenic variations. (November 2015) - Fagertun, Jens; Wolffhechel, Karin; Pers, Tune H.; Nielsen, Henrik B.; Gudbjartsson, Daniel; Stefansson, Hreinn; Stefansson, Kári; Paulsen, Rasmus R.; Jarmer, Hanne
Abstract : Highlights: We predict facial traits from genetic variants of 1300 individuals. We use information from large sets of SNPs. Six facial traits, facial width among others, are predicted significantly. This work is a promising addition to previous research into facial trait prediction. Abstract: Research into the importance of the human genome in the context of facial appearance is receiving increasing attention and has led to the detection of several Single Nucleotide Polymorphisms (SNPs) of importance. In this work we attempt a holistic approach predicting facial characteristics from genetic principal components across a population of 1266 individuals. For this we perform a genome-wide association analysis to select a large number of SNPs linked to specific facial traits, recode these to genetic principal components and then use these principal components as predictors for facial traits in a linear regression. We show in this proof-of-concept study for facial trait prediction from genome-wide SNP data that some facial characteristics can be modeled by genetic information: facial width, eyebrow width, distance between eyes, and features involving mouth shape are predicted with statistical significance ( p < 0.03).